The role early-life conditions in the cognitive decline due to adverse events later in life - Gerard J. van den Berg; Dorly J. H. Deeg; Maarten Lindeboom; France Portrait (Institute for Labour Market Policy Evaluation (IFAU), 2010)
Serious life events, such as the loss or the onset of a chronic condition may influence cognitive functioning. We examine whether the cognitive impact of such events is stronger if conditions very early in life were adverse, using Dutch lnogitudinal data of older persons. We exploit exogenous variation in early-life conditions as generated by the business.
Keywords: I12; I10; J14; E32; 330; Cognitive functioning; business cycle; bereavement; developmental origins; retirement; health; long-run effects; pension; dementia; Kognitive Fähigkeiten; Gesundheit; Lebensverlauf; Schock; Konjunktur; Niederlande